Doxorubicin-induced oxidative injury of cardiomyocytes - do we have right strategies for prevention? - Milic Torres, Vukosava (2012)
Anthracyclines are among the most utilised antitumour drugs ever developed. The discovery of one of the leading compounds, doxorubicin (DOX) in early 1960s was a major advance in the fight against cancer. According to the WHO, it belongs to the group of 17 essential drugs that are used to treat curable cancers or cancers for which the cost-benefit ratio clearly favours drug treatment (Sikora et al., 1999). It is used, often with other antineoplastic, in the treatment of Hodgkin's disease, non-Hodgkin's lymphomas, acute leukaemias, bone and soft-tissue sarcoma, neuroblastoma, Wilm's tumour, and malignant neoplasms of the bladder, breast, lung, ovary, and stomach. The mechanisms of cytotoxicity of DOX in cancer cells is complex including: inhibition of both DNA replication and RNA transcription; free radicals generation, leading to DNA damage or lipid peroxidation; DNA cross-linking; DNA alkylation; direct membrane damage due to lipid oxidation and inhibition of topoisomerase II (Gewirtz, 1999; Minotti et al., 2004). Today, topoisomarase II is generally recognized to be the cellular target of DOX, which act by stabilizing a reaction intermediate in which DNA strands are cut and covalently linked to this enzyme (Simunek et al., 2009). It blocks subsequent DNA resealing. Failure to relax the supercoiled DNA blocks DNA replication and transcription. Furthermore, DNA strand breaks may trigger apoptosis of cancer cells. However, as with all traditional antineoplastic drugs, DOX administration is accompanied by adverse drug reactions arising from the limited selectivity of their anticancer action (Aronson et al., 2006; McEvoy et al., 2010). Particularly common are bone marrow depression, which may be dose-limiting. White cell count reaches a nadir 10 to 15 days after a dose and usually recovers by about 21 days. Gastrointestinal disturbances include moderate or sometimes severe nausea and vomiting; stomatitis and oesophagitis may progress to ulceration. Alopecia occurs in the majority of patients. Occasional hypersensitivity reactions may also occur. However, a cumulative-dose dependent cardiac toxicity has been a major limitation of DOX use.